Nanoparticle‐Loaded Protein–Polymer Nanodroplets for Improved Stability and Conversion Efficiency in Ultrasound Imaging and Drug Delivery. (11th August 2015) - Lee, Jeong Yu; Carugo, Dario; Crake, Calum; Owen, Joshua; de Saint Victor, Marie; Seth, Anjali; Coussios, Constantin; Stride, Eleanor
<x xml:space="preserve">Abstract</x> A new formulation of volatile nanodroplets stabilized by a protein and polymer coating and loaded with magnetic nanoparticles is developed. The droplets show enhanced stability and phase conversion efficiency upon ultrasound exposure compared with existing formulations. Magnetic targeting, encapsulation, and release of an anticancer drug are demonstrated in vitro with a 40% improvement in cytotoxicity compared with free drug.